Stress at work - Quick, James Campbell; Nelson, Debra L. (Henry Stewart Talks, 2012)
Definitions of stress, Sources of stress, Modifiers of the stress response, Psychophysiology of stress, Stress benefits and costs, Individual distress, Organizational distress, Positive practices for achievement of total health, Workplace surveillance for stress, Preventive stress management methods, Primary, secondary, tertiary prevention